SURVEY OF GREEN LEAFY VEGETABLES IN KOLLEMCODE, KANYAKUMARI DISTRICT, TAMIL NADU. (International Journal of Food and Nutritional Sciences, 2022)
Green Leafy Vegetables (GLVs) are rich source of many nutrients and designated as nature’s anti-aging wonders. GLVs (Green Leafy Vegetables) have excellent medicinal benefits. Concentration of functional compounds vary according to the climate season, their growth phase and their existence in particular plant part. Total 30 plant species collected belonging to 20 families and 30 genera from the study area, Kollemcode. 20 family tabulated based on botanical name, common name and mode of consumption. Among them, five plants belong to the family Amaranthaceae, followed by Apiaceae with 3 plant species, Fabaceae, Phyllanthaceae, Rutaceae, Araceae with 2 plant species. Most of the plants are herb (24 plant species) among them the remaining plants are shrub, (4 plant species), tree (1 plant species), climber (2 plant species). Among the 30 GLVs plants 16 are cultivated plants, 7 as wild and 8 as wild/cultivated. Mostly the leafy part of the plant species is used for cooling purpose and presents the medicinal uses.